PENYULUHAN DAN PEMBUATAN JAMU TRADISIONAL DI DESA KEMIREN, BANYUWANGI 2022 - Azmi Prasasti; Sari Prayudeni; Stephanie Devi Artemisia; Titis Sriyanti; Avil Faisally; Fira Rizkia Sundari; Anggie Andina Ritansa (Jurnal SADEWA, 2023)
Utilization of natural materials into a herbal product is the goal of community service carried out by the Stikes Banyuwangi D3 Pharmacy team. The herbs made are beras kencur, kunyit asam, galian singset, and kunci sirih. Herbal medicine is very closely related to improving public health, especially for rural communities. Turmeric, ginger, galangal, bangle rhizome, piper betle leaf, jati belanda leaf and tamarind are natural ingredients that are made in the manufacture of herbal medicine. These natural materials are obtained from the area around Kemiren Village. The implementation time will take place on June 17, 2022 in Kemiren Village, Banyuwangi. The target of the activities women sosiality in PKK Kemiren Village.